Neuronal biomolecular condensates and their implications in neurodegenerative diseases - Nam, Jeongyeon; Gwon, Youngdae (Frontiers in Aging Neuroscience, 2023)
Biomolecular condensates are subcellular organizations where functionally related proteins and nucleic acids are assembled through liquid–liquid phase separation, allowing them to develop on a larger scale without a membrane. However, biomolecular condensates are highly vulnerable to disruptions from genetic risks and various factors inside and outside the cell and are strongly implicated in the pathogenesis of many neurodegenerative diseases. In addition to the classical view of the nucleation-polymerization process that triggers the protein aggregation from the misfolded seed, the pathologic transition of biomolecular condensates can also promote the aggregation of proteins found in the deposits of neurodegenerative diseases. Furthermore, it has been suggested that several protein or protein-RNA complexes located in the synapse and along the neuronal process are neuron-specific condensates displaying liquid-like properties. As their compositional and functional modifications play a crucial role in the context of neurodegeneration, further research is needed to fully understand the role of neuronal biomolecular condensates. In this article, we will discuss recent findings that explore the pivotal role of biomolecular condensates in the development of neuronal defects and neurodegeneration.